Strategi UMKM Untuk Bangkit dan Naik Kelas Dengan Akuntansi di Era Pandemi Covid-19 - Haviz Taufik; Eka Julianti ES; Vera Amalia (JAKU (Jurnal Akuntansi & Keuangan Unja) (E-Journal), 2023)
The purpose of this study is to find out the UMKM Strategy so that they can rise in the Covid-19 pandemic era with accounting and how UMKM can advance to class with accounting in the Covid-19 Pandemic Era. The sample in this study was 86 (eighty six) UMKM in Jambi City. The data in this study are primary and secondary data. The analytical method used is descriptive qualitative. The results of the study show that accounting can be a strategy for UMKM to rise in the era of the covid-19 pandemic through the presentation of financial statements in accordance with accounting standards in Indonesia and accounting can make UMKM advance through the presentation of financial statements in accordance with accounting standards in Indonesian.